Sila Pertama Pancasila guna Menumbukan Toleransi Keberagaman di SMA Negeri 3 Boyolali - Riyanti, Ratna Dwi; Putri, Azahra Nayla; Al Bukhori, Mario Ahmad; Marliyana, Shilvie; Fanie Yuniar Krismonita (Faculty of Cultural Studies, Universitas Brawijaya, 2025)
This socialization activity emphasizes that religious harmony must be maintained and carried out well becausereligious harmony will create harmony between diverse communities to create peace in Indonesia which is verydiverse. 1) The importance of implementing the first principle in fostering an attitude of tolerance betweenreligious communities. 2) Efforts to minimize the occurrence of bullying between students, it is hoped that allstudents can work together. 3) This socialization uses qualitative methods, observation and interviews. 4) Theconclusions of the results of this socialization are 1. Introducing the first value of Pancasila, 2. Carrying outsocialization activities and discussion forums, 3. Providing exemplary attitudes for students